Effects of egg incubation methods on locomotor performances of green turtle (Chelonia mydas) hatchlings - Mohd Uzair Rusli; Juanita Joseph; Hock, Chark Liew; Zainudin Bachok (Universiti Kebangsaan Malaysia, 2015)
Effects of different incubation methods on crawling and swimming ability of post-emergence green sea turtle (Chelonia mydas) hatchlings at Cherating (Kuantan, Pahang) and Chagar Hutang (Pulau Redang, Terengganu) Turtle Sanctuary were analysed during nesting season in 2009. Mean crawling speed of hatchlings incubated in styrofoam box, beach hatchery and in situ were at 0.042±0.008, 0.136±0.026 and 0.143±0.045 m/s, respectively. Crawling performance of hatclings from styrofoam box can be improved by keeping them for at least 48 h after their emergence. For swimming performance, all types of incubation methods showed significant differences in mean power-stroke rate during their early swimming effort ranging at 93-114 strokes/min. However, no correlation was found between morphological characteristics of hatchlings and swimming performance. The results from this study may give different perspective in evaluating hatchling production, which is in terms of hatchling morphological characteristics and their locomotor performance.